Psychological and Sociocultural of Breastfeeding Mothers in Exclusive Breastfeeding - Kusuma, Nur Intan; Kristiyanti, Rini; Ayuanda, Leila Nisya (Jurnal Bidan Cerdas, 2024)
Introduction: Breastfeeding mothers often face challenges, particularly psychological and sociocultural barriers. Globally, maternal mental health and sociocultural factors are major concerns in exclusive breastfeeding. This study aimed to identify the psychological and sociocultural conditions of breastfeeding mothers in providing exclusive breastfeeding. Methods: A purposive sampling technique was used to select 144 breastfeeding mothers with infants aged 6–12 months. Data collection was conducted using a questionnaire in July–August 2024. Data were analyzed using univariate, bivariate, and multivariate statistical methods. Results: The results showed that exclusive breastfeeding was significantly influenced by maternal psychological conditions (p=0.044), attitudes towards breastfeeding myths and beliefs (p=0.028), cultural practices (p=0.001), and social practices (p=0.007). Multivariate analysis confirmed that maternal psychological conditions, attitudes towards breastfeeding myths and beliefs, and cultural practices collectively influenced exclusive breastfeeding. Good cultural practices were identified as a key factor in successful exclusive breastfeeding Conclusion: A comprehensive approach is needed to promote positive cultural practices through family-based education. Additionally, active involvement of husbands and families is crucial in providing optimal support to ensure mothers are in a stable psychological and sociocultural condition, enabling them to successfully practice exclusive breastfeeding.